Interações e práticas em coletivos cidadãos voltados à transformação social no cenário sociodigital brasileiro: estudo de caso do coletivo POA Inquieta - Freitas, Cláudio Kury (Universidade do Vale do Rio dos Sinos, 2025)
The main objective of this thesis is to analyze the collective construction and citizen practice, under sociodigital interactions and perspectives, through the case study of the Porto Alegre Inquieta Collective and its articulated dynamics of social transformation, understanding in practice its model, potentialities and limitations. The work also presents as a backdrop the subcategory of sociology, called digital sociology, a recent academic construct that endorses the context of formation and performance of collective actions and projects focused on the city. The theoretical framework added to the construction and execution of the qualitative approach research took place between 2021 and 2023. Initially, an in-depth interview script was formulated. There were 16 interviews in total with active actors with a greater or lesser degree of participation in the collective, in addition to alumni. After conducting the interviews, it was possible to extract categories of analysis, as well as obtain subsidies for the creation of a robust research instrument. To validate perceptions and categories, responses to the questionnaires were collected and studied, given by a robust sample of 128 people. The categories of dynamics and articulation, interaction and collaboration, individual and collective transformation, sociodigital communication, politics and sustainability were reinforced. From the perspective of digital sociology, two typologies gained greater prominence: sociological analyses of digital use and critical digital sociology. The six categories of analysis were maintained in the larger investigation: dynamics and articulation; interaction and communication; individual and collective transformation; sociodigital communication; politics; sustainability. The object of study, the epistemological and methodological journey are duly based on the observance of classical theory and the introduction of contemporary theories, with due contextualization, based on the studies of Georg Simmel, Manuel Castells and Deborah Lupton. As a theoretical contribution, the path is paved for the continuation of studies under the lens of digital sociology, investigating and deepening the model presented here, and replicating it in other collective initiatives and other social phenomena of the present times in preparation for a present and future understanding. As an empirical contribution, the replication and adaptation of the research instrument to other formats of social innovation are suggested, to be able to extract knowledge from them and improve their results for society through an emancipatory and citizen vision.
Keywords: Sociologia digital; Porto Alegre Inquieta; Ação coletiva; Porto Alegre; Digital sociology; Collective action; ACCNPQ::Ciências Humanas::Sociologia